2013
DOI: 10.1142/s1469026813500053
|View full text |Cite
|
Sign up to set email alerts
|

Improved Weight Fuzzy Time Series as Used in the Exchange Rates Forecasting of Us Dollar to Ringgit Malaysia

Abstract: Foreign exchange rate (forex) forecasting has been the subject of several rigorous investigations due to its importance in evaluating the benefits and risks of the international business environments. Many methods have been researched with the ultimate goal being to increase the reliability and efficiency of the forecasting method. However as the data are inherently dynamic and complex, the development of accurate forecasting method remains a challenging task if not a formidable one. This paper proposes a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Data preparation transforms the data sets so that their information content is best exposed to the next process. Many studies [14][15][16][17][18] in AR frequently uses single point values as data input in building forecasting model. However, most single point values use the average data where this data will affect the standard deviation.…”
Section: Construction Of Symmetry Triangular Fuzzy Number Based On Pementioning
confidence: 99%
See 1 more Smart Citation
“…Data preparation transforms the data sets so that their information content is best exposed to the next process. Many studies [14][15][16][17][18] in AR frequently uses single point values as data input in building forecasting model. However, most single point values use the average data where this data will affect the standard deviation.…”
Section: Construction Of Symmetry Triangular Fuzzy Number Based On Pementioning
confidence: 99%
“…To address the limitation, the fuzzy theory is introduced in the AR model building which solves the uncertainty issues. In previous literatures, the issue of uncertainty has been studied by several authors by introducing fuzzy theory [14][15][16][17][18]. For example, fuzzy inference system was used to create a new air quality index while autoregressive model used to predict future air quality condition.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ismail et al [2013] proposed that the sub-interval number is equal to the range at interval i divided by 1+3.3 log (f i ), (i = 1, 2, 3, 4). The modification of our proposed interval can be mathematically compared with the interval proposed in Efendi et al [2013] as shown below. …”
Section: Proposed Interval Length and Forecasting Algorithmmentioning
confidence: 99%
“…The advantage of the first model, besides not needing assumptions and explanatory variables for the data set, is that it can be used to forecast linguistic values [Song and Chissom (1993a)]. The univariate-FTS model has been frequently implemented to forecast real data in sectors such as education [Song and Chissom (1993b);Chen (1996);Singh (2007); Kuo (2009);Ismail and Efendi (2011)], economy [Yu (2005); Yu and Huarng (2008); Lee et al (2006); Efendi et al (2013); Sun et al (2015); Gholizade and Chafi (2015)], and energy [Bolturuk et al (2012); Alpaslan and Cagcag (2012); Azadeh et al (2012); Efendi et al (2015); Ismail et al (2015); Efendi and Deris (2017)]. The forecasting accuracy of this model is improved by modifying the interval numbers of the data set and using out-sample model for linguistic time series.…”
Section: Introductionmentioning
confidence: 99%
“…Passionate about ANN algorithm, Egrioglu [18] also proposed the Picture fuzzy time series model, and also used ANN to replace the construction of fuzzy logic relations. However, because of the inexplicability of artificial neural networks, many scholars still prefer traditional prediction methods, such as Tsaur [19] and Efendi [20] using Markov weight method for prediction, and Li [21,22] is based on hidden Markov chains and long-term models.…”
Section: Introductionmentioning
confidence: 99%